2019
DOI: 10.3390/f10050403
|View full text |Cite
|
Sign up to set email alerts
|

Mite Communities (Acari, Mesostigmata) in the Initially Decomposed ‘Litter Islands’ of 11 Tree Species in Scots Pine (Pinus sylvestris L.) Forest

Abstract: Replacement of native deciduous forests by coniferous stands was a common result of former European afforestation policies and paradigms of forest management and led to considerable ecological consequences. Therefore, the most popular management strategy nowadays in multi-functional forestry is the re-establishment of mixed or broadleaved forests with native species on suitable habitats. However, our knowledge about the effects of tree species introduced into coniferous monocultures on soil mesofauna communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…Finally, four papers focused on the management of forest pests. Kamczyc et al [27] studied Mesostigmata mite communities in the decomposed litter of broadleaved and coniferous trees, to evaluate the effects of the re-establishment of mixed or broadleaved forests with native species. The results revealed that the species richness and diversity of the mite community were not affected, but the mite abundance was influenced by the tree species, which suggests differences in the litter quality.…”
Section: Papers In This Issuementioning
confidence: 99%
“…Finally, four papers focused on the management of forest pests. Kamczyc et al [27] studied Mesostigmata mite communities in the decomposed litter of broadleaved and coniferous trees, to evaluate the effects of the re-establishment of mixed or broadleaved forests with native species. The results revealed that the species richness and diversity of the mite community were not affected, but the mite abundance was influenced by the tree species, which suggests differences in the litter quality.…”
Section: Papers In This Issuementioning
confidence: 99%
“…As many studies revealed, mesostigmatid mites feed primarily on herbivorous, fungivorous and saprophagous organisms (Koehler 1999 ; Wissuwa et al 2012 ; Skorupski et al 2013 ), which may be directly dependent on fallen litter features (Fujii and Takeda 2017 ; Kamczyc et al 2019 ; Urbanowski et al 2021 ). Moreover, microhabitat properties (Frouz 2018 ), including leaf structure (Schmidt 2014 ), as well as soil-forming processes, including forest litter decomposition (Osler et al 2004 ; Urbanowski et al 2018 , 2021 ), may significantly shape soil fauna communities, including mesostigmatid mites.…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition rates depend on climate, litter quality, and communities of soil organisms (Berg and McClaugherty 2014;Cornwell et al 2008;Kamczyc et al 2019;Urbanowski et al 2018). Microclimates in temperate deciduous forest understories vary during the growing season, due to changing solar zenith angle and canopy phenology (Noda et al 2015).…”
Section: Introductionmentioning
confidence: 99%